PKM SISTEM INFORMASI AKUNTANSI PEMBUATAN LAPORAN KEUANGAN BERBASIS WEB - Siti Kholifah (Pusat Riset dan Inovasi Nasional, 2022)
The problem that occurs in Adi jaya Grosir is that the administrative process and the making of the financial statements of profit or loss obtained by the administration officer must go through a manual and not integrated process. Difficulties occur in calculating the amount of income earned by each sales. And it is difficult to know the number of stores that actively order products from this because there is no accounting information system, so the process is still manual. In this study the software used to build the system is Balsamiq Mockups for designing systems, PHP programming scripts and using MySQL as the database. The results obtained are financial data recapitulation. The system provides a report menu that is integrated between sales transaction data and financial statement data, so that it can obtain reports based on date. This system also generates income reports for each salesperson. With this system, the operation manager and administration staff can see the number of stores / customers who are actively ordering products from Adi jaya Grosir. This system produces accurate financial reports because the process is integrated. Reports generated by accounting information systems for making web-based financial statements can be printed and exported in the form of a .pdf file.